2020
DOI: 10.1158/1078-0432.ccr-20-4084
|View full text |Cite
|
Sign up to set email alerts
|

Phase IB Study of Osimertinib in Combination with Navitoclax in EGFR-mutant NSCLC Following Resistance to Initial EGFR Therapy (ETCTN 9903)

Abstract: Purpose: Osimertinib is an effective therapy in EGFR-mutant non–small cell lung cancer (NSCLC), but resistance invariably develops. Navitoclax is an oral inhibitor of BCL-2/BCL-xL that has exhibited synergy with osimertinib in preclinical models of EGFR-mutant NSCLC. In hematologic malignancies, BCL-2 family inhibitors in combination therapy effectively increase cellular apoptosis and decrease drug resistance. Patients and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…A phase II trial of gefitinib with chemotherapy or antiangiogenesis as front-line therapy is no-going in BIM-del EGFR-mutant NSCLC patients (NCT03267654). Other potential drugs like selective BCL-2/BCL-xL inhibitors, as proapoptotic agents, could re-sensitize resistant cell lines to osimertinib in vitro and improve PFS in pretreated T790M patients [33][34][35]. Clinical trials are needed in EGFRmutant patients with BIM-del.…”
Section: Key Pointsmentioning
confidence: 99%
“…A phase II trial of gefitinib with chemotherapy or antiangiogenesis as front-line therapy is no-going in BIM-del EGFR-mutant NSCLC patients (NCT03267654). Other potential drugs like selective BCL-2/BCL-xL inhibitors, as proapoptotic agents, could re-sensitize resistant cell lines to osimertinib in vitro and improve PFS in pretreated T790M patients [33][34][35]. Clinical trials are needed in EGFRmutant patients with BIM-del.…”
Section: Key Pointsmentioning
confidence: 99%
“…One concern regarding ABT-263 in the clinic is the thrombocytopenia that has been a predominant dose limiting toxicity as both a monotherapy and in combination. This has been managed successfully in several recent trials, allowing for tolerated and biologically active combinations with kinase inhibitors such as Osimertinib (Bertino et al, 2021) and ruxolitinib (Harrison et al, 2019). However, neutropenia has been reported as a dose limiting toxicity when navitoclax was administered with chemotherapy (Puglisi et al, 2011); this toxicity has been particularly limiting for these combinations, none of which have progressed beyond Phase 1.…”
Section: Figure 6dmentioning
confidence: 99%
“…Clinical trials studying oral combination therapy with navitoclax and osimertinib in advanced EGFR-mutant NSCLC with prior TKI treatment have reported an ORR of up to 100% and a median PFS of 16.8 months. However, thrombocytopenia and lymphopenia were the most common adverse events (37%) observed in the study ( 110 ). Finally, it was found that C-FLIP knockdown restored osimertinib-induced apoptosis in resistant cells ( Table 1 ), suggesting that C-FLIP depletion may be an effective strategy to overcome osimertinib resistance in NSCLC ( 44 , 111 ).…”
Section: Apoptosis Modulatorsmentioning
confidence: 94%